1992
DOI: 10.1177/08959374920060010101
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Dental Amalgams and the Oral Environment

Abstract: Dental amalgam fillings interact in a complex way with the environment in the oral cavity as they are subjected to chemical, biological, mechanical, and thermal forces. These forces change the restoration's appearance and properties, while metal ions, amalgam debris, non-metallic corrosion products, and mercury vapor are released into the oral cavity. The phenomena and conditions that affect the amalgam/environment interaction include the chemistry and biochemistry of the environment, formation of biofilms on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 49 publications
2
27
0
2
Order By: Relevance
“…All these factors act continuously or intermittingly and their effect can be complex. 14 One of the major outcomes of these interactions is release of corrosion products from the amalgam restorations. On one hand, corrosion is regarded as an adverse phenomenon.…”
Section: Pathways Of Transport Of Metal Ions Into and Along Dentinmentioning
confidence: 99%
“…All these factors act continuously or intermittingly and their effect can be complex. 14 One of the major outcomes of these interactions is release of corrosion products from the amalgam restorations. On one hand, corrosion is regarded as an adverse phenomenon.…”
Section: Pathways Of Transport Of Metal Ions Into and Along Dentinmentioning
confidence: 99%
“…7,8,9,10,11 Corbin and Kohn 12 state that many researchers have found that mercury vapour released from amalgam restorations varies from 1.24 -27 µg/day. While most of the researchers agree that current evidence does not demonstrate that amalgam restorations are hazardous to the health of the general population, some report that mercury release from amalgam is one of the important sources of inorganic mercury.…”
mentioning
confidence: 99%
“…Ogawa et al 15) examined the charging and discharging curves of conventional and highcopper amalgams in 0.9 mass% sodium chloride solution and reported that most of the released tin ions existed as tin oxides on the surface of the amalgams. Marek 1) also revealed that the γ 1 phases on an amalgam surface were covered with tin oxide films in the oral cavity. Generally, the γ 2 phase dissolves following eq.…”
Section: Decrease Of Released Ionsmentioning
confidence: 99%
“…1,10,11,13) Marek 1) revealed that the γ and the ε phases are thermodynamically more stable than either the γ 2 or η phase. Onagawa and Abe 13) examined the electrochemical stability of each phase existing in conventional and high-copper amalgams using their anodic polarization curves in 0.9 mass% sodium chloride solution.…”
Section: Preferentially Dissolved Phasementioning
confidence: 99%
See 1 more Smart Citation